(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Understanding the evolutionary trajectory of women’s rights throughout the civilizing process means, mainly, getting used to them as historical-secondary characters, considering that they were relegated, for millennia, to the smallest political-social performance, being impelled to incorporate archaic, deeply incorporated and rooted in the collective imaginary of societies over time, which are permeated by the demands that oblige them to be subservient and submissive to the men of their circumscription of experience. Consequently, invisibility and oppression have become commonplace in the female reality, becoming impediments to the achievement of substantial human rights, intrinsic to the concretization of citizenship status. Consider the context outlined, it is intended, through this contemporary legal article, to talk about the legal-social condition of women before the promulgation of the 1916 juscivilist statute, showing the violence perpetrated by the positive right to the female elements of society at the time, in order to understand the system of Brazilian patriarchalism that reverberates negatively in the experience of Brazilian women today, in the same way that aims to apprehend the need to invest in public policies in favor of social minorities, corroborating the struggle and the yearnings of the movement feminist.